Unexpected Postpartum Hemorrhage Due to an Acquired Factor VIII Inhibitor - Paidas, Michael J.; Hossain, Nazli (American Journal of Perinatology, 2014)
Unexplained postpartum hemorrhage (PPH) refractory to standard hemostatic measures should trigger a heightened clinical suspicion of an acquired bleeding disorder. When hemostatic medical interventions and surgical procedures fail to control the bleeding, then significant postoperative blood loss, debilitating morbidity, loss of fertility, and death may occur. In the setting of an autoantibody inhibitor to factor VIII (FVIII), control of life-threatening PPH and avoidance of subsequent bleeding episodes depends on a timely and accurate diagnosis, prompt hemostatic treatment and eradication of FVIII inhibitors, and appropriate long-term patient care and management. Acquired postpartum hemophilia due to a FVIII inhibitor is a rare cause of PPH; however, delayed treatment can lead to increased maternal morbidity and mortality. Acquired FVIII inhibitors also pose an emerging bleeding threat to the neonate as a result of possible transplacental transfer of FVIII autoantibodies to the fetus during the last trimester of pregnancy. The purpose of this review is to increase awareness among hematologists and obstetricians/gynecologists regarding the occurrence of FVIII neutralizing autoantibodies as a cause of PPH, and emphasize the importance of collaboration between obstetrician/gynecologists and hematology specialists to optimize the diagnostic evaluation, treatment, and long-term management of women who experience PPH due to an acquired FVIII inhibitor.
Keywords: factor VIII; acquired hemophilia; pregnancy; antibodies; postpartum hemorrhage